The problem of creating a common educational space: eurasian dimension (International relations and international law Journal, 2016)
Article is devoted to the creation of the Eurasian common educational space. Establishing of a common educational space as an aspect of integration is a topical issue for our region as well. In contrast to the formation and development of a common educational space in other regions of the world, the integration processes in the Eurasian region have their own characteristics. The development of historically unified educational space has always been one of the main areas of cooperation Eurasian countries. Many years of common historical destiny, traditions and experience of cohabitation, economic and cultural, human relations – all this is fertile ground for the creation of a common educational space of the newly independent states.The article deals with the problems and difficulties of creating a common educational space.
Keywords: education; educational space; Eurasian dimension; the Eurasian Union